Austrian Observations of Luzon in the 1878 Book Fragments Concerning a Geology of the Island of Luzon by Richard Freiherr von Drasche-Wartinberg, Translation of Chapter 6: Benguet - Goddard-Paz, Lisa Elena (Social Science Diliman: A Philippine Journal of Society and Change; Vol 19 No 2 (2023), 2025)
Since the 1860s, German-speaking scholars have visited the Philippines. Philippine historians now recognize their contributions to the study of the Spanish colony, its islands, and inhabitants. These scholars included Austrian nationals, among them the relatively unknown Richard Freiherr von Drasche-Wartinberg. Von Drasche visited the Philippines in 1878 and published his geological findings in his book Fragmente zu einer Geologie der Insel Luzon (Philippinen). Mit einem Anh. über die Foraminiferen der tertiäeren Thone von Luzon von Felix Karrer (Fragments concerning a Geology of the Island of Luzon (Philippines). With an Appendix Concerning the Foraminifers of the Tertiary Clays of Luzon by Felix Karrer). While it contributes to studies of the Philippines, research has so far uncovered only snippets of English translations of the original. This research note introduces and contextualizes the book, particularly the sixth chapter concerning Benguet, which it translates for scholars who require an English language copy of the text. To facilitate comparison with the original and convey its particular character, the translation aims to remain true to the content, writing style, and formatting of the original text.